Investigation of heat transfer coefficients in a liquid–liquid direct contact latent heat storage system. (April 2020) - Kunkel, Sven; Teumer, Tobias; Dörnhofer, Patrick; Wunder, Frederik; Repke, Jens-Uwe; Rädle, Matthias
Highlights: The temperature profile of a rising droplet was determined with 2000 measurements per seconds. The droplet geometry and flow velocity remain constant over the PCM height. The heat transfer coefficient between oil and liquid PCM is constant over the entire PCM height. The heat transfer coefficient between oil droplet and liquid PCM is 1845 W/m² K Abstract: The study presents a latent heat storage system consisting of a phase change material (PCM) and a heat transfer fluid (HTF), placed in direct contact, for storing thermal energy derived from renewable energy sources or industrial waste heat. It is important that the two media are immiscible for the function of such a storage system. In this study the PCM was an eutectic mixture of the two salt hydrates, magnesium nitrate hexahydrate and magnesium chloride hexahydrate and the HTF was a mineral oil. The direct contact leads to intensified heat transfer compared to that in the indirect contact heat storage systems. This intensified heat transfer results in short loading and unloading periods of the storage tank with a high heat exchange performance. Furthermore, a higher storage density is observed in comparison to the sensible storage systems, particularly when combined with low temperature differences between the charged and discharged storage systems. In our study, the heat transfer between liquid PCM and liquid HTF (rises drop-shaped in the PCM) is investigated. For this purpose, a storage tank has been built with only one HTF inlet opening in the bottom. For the time and space resolved data, the axial temperature profile, and the surface temperature of the rising droplet, as well as the PCM temperature, are measured with a specially developed, fast, near infrared sensitive, and fiber-coupled technique. These measurements made it possible to determine a local heat transfer coefficient between the PCM and HTF. With the chosen parameters and materials in this study a heat transfer coefficient of 1845 W/m² K was calculated.